1994
DOI: 10.1002/ceat.270170607
|View full text |Cite
|
Sign up to set email alerts
|

Liquid velocity and dispersion coefficient in an airlift reactor with inverse internal loop

Abstract: An airlift reactor with inverse internal loop (annulus sparged) is investigated with regard to liquid velocity and dispersion coefficient for the purpose of reactor design. To distinguish between the influence of the individual parts of the reactor (downcomer, riser, bottom) on the liquid velocity and mixing, several draft tubes with different geometries and draft tube bottom clearances are successively installed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Over the ranges of packing matrices, packing height, bed top, and bottom bed clearances used in this investigation, these features seem to be influence the liquid axial dispersion coefficient in the fibrous‐bed bioreactor. The dependence of liquid axial dispersion coefficient on the liquid circulation velocity in the ILALFBB proposed in this study could be accurately modelled by a modified empirical correlation previously suggested by Kochbeck and Hempel (1994) for unpacked ILAL‐bioreactor which describes the dependence of axial dispersion coefficient on the liquid circulation velocity ( U Lr /U L,I ) and the area ratio ( A r / A d ). In the current study, this model was based on 107 experimental data in each case.…”
Section: Correlationsmentioning
confidence: 78%
“…Over the ranges of packing matrices, packing height, bed top, and bottom bed clearances used in this investigation, these features seem to be influence the liquid axial dispersion coefficient in the fibrous‐bed bioreactor. The dependence of liquid axial dispersion coefficient on the liquid circulation velocity in the ILALFBB proposed in this study could be accurately modelled by a modified empirical correlation previously suggested by Kochbeck and Hempel (1994) for unpacked ILAL‐bioreactor which describes the dependence of axial dispersion coefficient on the liquid circulation velocity ( U Lr /U L,I ) and the area ratio ( A r / A d ). In the current study, this model was based on 107 experimental data in each case.…”
Section: Correlationsmentioning
confidence: 78%
“…The differences derive also from the methods used for the estimation of D ax . Most contributions are indeed based on the Blenke method (see, e.g., Blenke, 1979;Fields and Slater, 1983;Kochbeck and Hempel, 1994;Tudose, 1996, 1997;Merchuk et al, 1998) that considers an axial dispersion coefficient for the whole reactor. This method is probably suitable for internal-loop ALRs, for which deaeration is seldom complete, but this point is more doubtful in external-loop ALRs, as shown by Verlaan et al (1989), Lu et al (1994) and Dhaouadi et al (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Further, if a strong white noise was added to the measured RTD data, the calculated parameter deviated from the real value and could not represent the real flow behavior in the reactor. Although many researchers have studied the reliability of the data processing methods mentioned above [3][4][5][6], few of them have discussed the anti-disturbance ability of these methods. Therefore, it is important to find a robust method to calculate the fluid velocity and dispersion coefficient from raw experimental RTD data.…”
Section: Introductionmentioning
confidence: 99%